Investigating methane adsorption potential of Malaysian coal for coal bed methane (CBM) study - Tunio, S.Q. (Mediterranean Center of Social and Educational Research, 2014)
Methane in coal can be present as free gas or as an adsorbed layer in the internal surfaces of the coal micropores. Methane gas is adsorbed to the internal surface area of the coal associated with high pressure and exists as a monomolecular layer on the internal surface of the coal matrix. The only way to produce these gasses is by reducing the pressure within the coal matrix until the gas can be desorbed. A comparative study is made on the adsorption potential of methane gas in Malaysian coal with other producing CBM basins. The Langmuir isotherm shows that the amount of methane adsorbed in Sarawak coal is 14.11 scf/tonne at 36 psia where as in Piceance basin it amounts to 30 scf/tonne at 36 psia and in Powder River Basin is 6.52 scf/tonne at 36 psia. This suggests Sarawak coals of Malaysia also possess comparable methane adsorption potential to other producing CBM fields. Results also suggest that the adsorption amount depends on depth only for particular coal but the amount does not depend on the depth of varieties of coal. Therefore Malaysian coal will be successful CBM producer only if it has got the source of methane at greater depth. Â© 2014, Mediterranean Center of Social and Educational Research. All rights reserved.